Discussing Questions of Laser Refractive Surgery in Hyperopia: Literature Review and Clinical Experience - N. V. Maychuk; I. A. Mushkova; I. S. Malyshev; M. R. Obraztsova (Oftalʹmologiâ, 2022)
Relevance. Modern keratorefractive surgery is a high-tech field of ophthalmology aimed at solving various problems of correcting a wide range of ametropias.Objective: to formulate recommendations for refractive surgeons when planning the correction of hypermetropic refraction using modern keratorefractive surgery.Materials and methods. An analysis of 20 literature sources and a retrospective analysis of outpatient records of 188 patients with hypermetropia who underwent surgery were carried out.Results. The analysis of the literature and our own clinical study allows us to recommend focusing on the final keratometry after keratorefractive surgery, which should not exceed 48 diopters. Among the analyzed charts of patients in compliance with these criteria, the accuracy of hitting the target refraction in the range of ± 1 D was 98.9 %, the regression did not exceed 0.5 D from that obtained 1 month after surgery in 96.8 %, and the loss of 1 line of BCVA was 3.7 % of cases. Among patients with achieved keratometry above 48 diopters, the loss of line 1 BCVA was 13.8 %, line 2 — 2.7 %.Conclusion. Thus, the tactics of correction of hypermetropia by CRC methods require an integrated approach to the assessment of visual functions, drug preparation for surgery, careful implementation of the surgical stages of the intervention, and rational postoperative pharmacological support.